ALS-linked mutant TDP-43 in oligodendrocytes induces oligodendrocyte damage and exacerbates motor dysfunction in mice - Mai Horiuchi; Seiji Watanabe; Okiru Komine; Eiki Takahashi; Kumi Kaneko; Shigeyoshi Itohara; Mayuko Shimada; Tomoo Ogi; Koji Yamanaka (Acta Neuropathologica Communications)
Abstract Nuclear clearance and cytoplasmic aggregation of TAR DNA-binding protein of 43 kDa (TDP-43) are pathological hallmarks of amyotrophic lateral sclerosis (ALS) and its pathogenic mechanism is mediated by both loss-of-function and gain-of-toxicity of TDP-43. However, the role of TDP-43 gain-of-toxicity in oligodendrocytes remains unclear. To investigate the impact of excess TDP-43 on oligodendrocytes, we established transgenic mice overexpressing the ALS-linked mutant TDP-43M337V in oligodendrocytes through crossbreeding with Mbp-Cre mice. Two-step crossbreeding of floxed TDP-43M337V and Mbp -Cre mice resulted in the heterozygous low-level systemic expression of TDP-43M337V with (Cre-positive) or without (Cre-negative) oligodendrocyte-specific overexpression of TDP-43M337V. Although Cre-negative mice also exhibit subtle motor dysfunction, TDP-43M337V overexpression in oligodendrocytes aggravated clasping signs and gait disturbance accompanied by myelin pallor in the corpus callosum and white matter of the lumbar spinal cord in Cre-positive mice. RNA sequencing analysis of oligodendrocyte lineage cells isolated from whole brains of 12-month-old transgenic mice revealed downregulation of myelinating oligodendrocyte marker genes and cholesterol-related genes crucial for myelination, along with marked upregulation of apoptotic pathway genes. Immunofluorescence staining showed cleaved caspase 3–positive apoptotic oligodendrocytes surrounded by activated microglia and astrocytes in aged transgenic mice. Collectively, our findings demonstrate that an excess amount of ALS-linked mutant TDP-43 expression in oligodendrocytes exacerbates motor dysfunction in mice, likely through oligodendrocyte dysfunction and neuroinflammation. Therefore, targeting oligodendrocyte protection, particularly through ameliorating TDP-43 pathology, could represent a potential therapeutic approach for ALS.